The importance of diet, intestinal microbiome and physical activity in Rheumatoid Arthritis (RA) - Review - Antczak, Joanna; Lipska, Julia; Hamerska, Laura; Hamerska, Julia; Bocianiak, Bogumił; Kajka, Anna; Fenrych, Urszula; Wojtczak, Karolina; Skupińska, Olga; Ruta, Damian (Quality in Sport, 2024)
Introduction and objective Rheumatoid arthritis (RA) is an autoimmune disorder characterized by chronic inflammation and joint damage resulting from an excessive production of inflammatory cytokines. The objective of this text is to describe the interplay between the gut microbiome, dietary factors, physical activity and RA pathogenesis. By synthesizing current knowledge, we aim to provide potential insights into the development of personalized therapeutic strategies to improve outcomes for individuals with RA. Review methods Literature review was carried out using PubMed, Scopus and Google Scholar databases. The following search terms were used: “rheumatoid arthritis gut microbiome”, “rheumatoid arthritis diet”, “rheumatoid arthritis sport”. Articles published from 2016 to 2023 were analyzed. Earlier articles were sometimes included, if referenced by later works. State of knowledge While there is no cure for RA, several treatments aim to manage its symptoms and improve quality of life for those affected. The most common treatments include medications: nonsteroidal anti-inflammatory drugs, disease-modifying anti-rheumatic drugs, corticosteroids. Recent attention has turned to the role of sport, diet, and the gut microbiome in modulating RA severity, offering promising avenues for holistic management approaches. Summary Recent research highlights the role of diet in modulating RA severity, with evidence suggesting alterations in gut microbiota composition in RA patients, including the impact of dietary interventions, probiotics, prebiotics, fecal microbiota transplantation, antibiotics, and vitamin D supplementation on the gut microbiome and their potential efficacy in mitigating RA-associated symptoms. Physical activity has also been shown to reduce the severity of RA symptoms.